Sinergi Pemerintah Desa dan Kawasan Industri dalam Pemberdayaan Masyarakat: Studi Kasus Desa Plenen - Karmanis Karmanis; Trilesctari Trilesctari; Karjono Karjono (Universitas 17 Agustus 1945 Semarang, 2026)
The development of industrial areas has direct implications for surrounding buffer villages, including Plenen Village, which is adjacent to the Batang Integrated Industrial Estate (KITB)/Batang Industropolis Special Economic Zone (SEZ). The main issue identified is the suboptimal utilization of industrial development opportunities to improve local community welfare. This study aims to analyze the synergy between village government and industrial areas in empowering the community of Plenen Village. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, field observations, and document analysis, and were analyzed thematically. The findings indicate that synergy between the village government and industrial area has been established through program coordination, facilitation of local labor absorption, and social support via corporate social responsibility programs. However, such synergy remains partial and has not been institutionally integrated, resulting in limited impact on community empowerment. The study concludes that strengthening collaborative governance and joint planning is essential to ensure that industrial development provides more inclusive and sustainable benefits for buffer village communities.